Hypochlorite Generation from a Water Softener Spent Brine - Daniela Sánchez-Aldana (Water, 2018)
Industries that require water with low hardness consume large amounts of NaCl for water softening. In this work, water softener spent brines were recovered and used as raw material in an electrolysis cell with cationic exchange membrane (CEM) to yield both sodium hypochlorite and sodium hydroxide amounts, which are the most common disinfectants used to sanitize production areas. Spent brines contained mainly an average of 4.5% NaCl, 650 mg L−1 Ca2+, and 110 mg L−1 Mg2+, the last two cations adversely affect the CEM and must be treated prior to the electrolytic process. Two hardness removal methods were evaluated separately—lime-soda ash and sodium hydroxide-soda ash softening—the last one being the most effective as total hardness was decreased by 99.98%. This pretreated spent brine was then introduced into the electrolysis cell. Experimental design comprised five level variations for current intensity, % NaCl, and time. The best operation conditions yielded 2800 mg L−1 NaOCl for a 5% NaCl solution. By incorporating chlorine gas trap to increase OCl− concentration a maximum of 7400 mg L−1 NaOCl was achieved. Finally, biocidal activity was tested following sanitation protocols (NaOCl dilution level) on workbenches and a decrease in bacterial count of at least 5 logs under laboratory-controlled conditions.